Comparative Analysis Between Economic Activity and Road Transport Safety – Insights from European Union Countries - ÖTVÖS, Viktoria; AL-MAHAMID, Hazem (Promet - Traffic&Transportation, 2026)
Road transport safety is a global concern, impacting public health, economic stability and quality of life. Understanding how economic growth and activity, represented by gross domestic product (GDP/capita), correlate with road safety outcomes is essential for crafting effective policies and interventions. This study investigates the complex relationship between gross domestic product (GDP/capita) and road safety in 27 European countries from 2005 to 2020. Using data on traffic fatalities per capita and vehicles, this research examines the influence of economic indicators on road safety outcomes, employing the original TRINCA model to frame the analysis within stages of economic development. The findings reveal that higher GDP levels are generally associated with improved road safety. However, the pace of these improvements varies significantly across European countries, reflecting diverse socio-economic contexts and regulatory frameworks. Cluster analysis classifies countries based on safety and economic performance, highlighting disparities in progress and opportunities for targeted interventions to prove the theoretical framework of the TRINCA model still exists. This study underscores the critical role of sustained economic growth and policy reform in achieving safer road systems.